1972
DOI: 10.1126/science.175.4018.191
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyls: Toxicity to Certain Phytoplankters

Abstract: The growth rates of two species of marine diatoms were reduced by polychlorinated biphenyls (PCB's), widespread pollutants of the marine environment, at concentrations as low as 10 to 25 parts per billion. In contrast, a marine green alga and two species of freshwater algae were not inhibited at these or higher concentrations. The sensitivity of these species to PCB's paralleled their sensitivity to DDT [1,1,1-trichloro-2,2-bis(p-chlorophenyl)ethane].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

1972
1972
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(20 citation statements)
references
References 19 publications
1
18
1
Order By: Relevance
“…He took an inoculum from a recove-red population and observed that it still displayed an initial period of no cell division. The algal species Skelatonema costatum did not divide for nine days following an initial dose of 80 parts per 10 9 DDT; this is unusual since MOSSER et al (1972) observed reduced but nonetheless substantial daily increases in cell numbers starting from day one in S. costatum cultures after an initial dose of 100 parts per 10 9 DDT. Moreover, MENZEL et al (1971) obtained similar result with a daily dosage of 100 parts per 10 9 DDT.…”
Section: B) E !Fects On Cell Divisionmentioning
confidence: 80%
See 1 more Smart Citation
“…He took an inoculum from a recove-red population and observed that it still displayed an initial period of no cell division. The algal species Skelatonema costatum did not divide for nine days following an initial dose of 80 parts per 10 9 DDT; this is unusual since MOSSER et al (1972) observed reduced but nonetheless substantial daily increases in cell numbers starting from day one in S. costatum cultures after an initial dose of 100 parts per 10 9 DDT. Moreover, MENZEL et al (1971) obtained similar result with a daily dosage of 100 parts per 10 9 DDT.…”
Section: B) E !Fects On Cell Divisionmentioning
confidence: 80%
“…Quantitative data were not given for these species. MOSSER et al (1972) grew Skelatonema costa tum and Thalassiosira pseudonana (Cyclotella nana) in cultures with 100 parts per 10 9 DDT, added initially. Significant differences between control and test culture cell numbers were noticed on days one and two for both species; by day three, cell numbers were not significantly different.…”
Section: B) E !Fects On Cell Divisionmentioning
confidence: 99%
“…Mahanty and Evans [13] described substantial toxic effect of PCBs and DDT on growth of soil microorganisms. The toxicity of PCBs parallels that of DDT, probably due to their similar chemical properties [14] and DDT + pp'DDE are known to have higher acute toxicity than PCBs [15].…”
Section: Resultsmentioning
confidence: 98%
“…The solubility, chemical stability, and apparent mobility of PCBs have resulted in environment movement comparable with that of several organochlorine insecticides [21].…”
Section: Page 4 Of 27mentioning
confidence: 99%